101 Multiple workload spikes and the risk of shoulder injuries in adolescent competitive tennis players: the SMASH cohort study. (3rd March 2020) - Skillgate, Eva; Cools, Ann; Fernandez-Fernandez, Jaime; Johansson, Fredrik
Abstract : Background: The role of training work load for injuries in sports, has been studied extensively, but the effect of repeated work load spikes on injury rate has to our knowledge not been studied. Objective: To estimate the effect of upward tennis and match training workload spikes (TWS), upward fitness training workload spikes (FWS) and the average number of hours of fitness training at baseline (FWB) on the risk of shoulder injuries in adolescent competitive tennis players. Design: Prospective cohort study. Setting and participants: 301 competitive Swedish tennis players, 13–19 years. Assessment of risk factors: The acute/chronic work-load ratio in tennis and fitness training respectively was calculated for each week. TWS and FWS were defined as an increase in the workload ratio. The cumulative number of TWS and FWS was categorized in sets of five to judge the dose response effect. FWB was defined as average hours of fitness training per week and categorized as low (<3.5 h) or high (≥3.5 h). Main outcome measurements: One-year weekly OSTRC Overuse Injury Questionnaires measured shoulder injuries. A sum score of ≥ 40 in the dominant shoulder was defined as an injury. Hazard Rate Ratios (HRR) with 95% Confidence Intervals (CI) was calculated with Cox regression analyses of multiple events, by formulation of Andersen and Gill and adjusted for age, gender and playing level. Results: For every additional five TWS or FWS, the HRR for a shoulder injury increased with 1.4 (95% CI: 1.0–2.0) and 1.5 (95% CI: 1.0–2.4), respectively. The HRR for low FWB was 1.0 (95% CI: 0.8–1.2), in comparison to high. Conclusions: Upwards spikes in tennis as well as fitness training may entail a higher shoulder injury rate in adolescent competitive tennis players. There is a dose response relationship there the more number of upward spikes, the higher the injury rate.